American, Swiss, Australian, Brazilian and French youth talk about their hopes and aspirations for the future. (RevistAleph, 2019)
The prolongation of that period of life referred to as youth is well documented andaccepted in the literature relating to youth. Dwyer and Wynn (2001) wrote of the newmeaning of adulthood and the problem facing youth as they make a transition to atarget zone that is constantly changing. The certainty of making a smooth transition toadulthood is no longer, if it ever were, assured. This study looks at a number of youthin what is often referred to as the transition phase to adulthood. They are in fivedifferent countries Brazil, France, Switzerland, Australia, and United States ofAmerica on four different continents. The individuals interviewed were generallybetween 18 – 30 years of age. They were asked a variety of questions relating to theirprospects, hopes and aspirations for the future.